The critics of modern money theory (MMT) are right - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
Eric Tymoigne and Randall Wray's (T&W, 2013) defense of MMT leaves the MMT emperor even more naked than before (excuse the Yogi Berra-ism). The criticism of MMT is not that it has produced nothing new. The criticism is that MMT is a mix of old and new, the old is correct and well understood, while the new is substantially wrong. Among many failings, T&W fail to provide an explanation of how MMT generates full employment with price stability; lack a credible theory of inflation; and fail to justify the claim that the natural rate of interest is zero. MMT currently has appeal because it is a policy polemic for depressed times. That makes for good politics but, unfortunately, MMT's policy claims are based on unsubstantiated economics.
urn:nbn:de:101:1-2014031112526
Keywords: E00; E02; E10; E12; E24; E40; E58; E62; E63; 330; modern money theory; money financed budget deficits; fiscal policy